Molecular Dynamics Study of Peptide in Water at Different Temperature - Chaudhary, U.; Kaphle, G. C. (Journal of Nepal Physical Society, 2023)
Molecular dynamics approach has been carried out to study the structural properties of peptide to estimate the self-diffusion coefficients of water at different temperatures 290 K, 300 K, and 310 K respectively. The energy profiles show the stability of system which ensures a well-balanced molecular structure of the system. The radial distribution functions (RDFs) of the solvent-solvent, solute-solute, and solute-solvent show the distribution of system within the required references. The self-diffusion coefficients of water have been determined using respective mean square displacement (MSD) curves through the Einstein’s relation. The self-diffusion coefficients of water at different temperatures are 0.44 ×10-5 cm2s-1, 0.48 ×10-5 cm2s-1, and 0.50 ×10-5 cm2s-1 respectively. Calculations show that the MSD of water throughout the system is increasing on increasing temperature. The results are also valid with the theoretical as well as available experimental data.